The Effect of Individual Workload Perceptions of Nurses Working in COVID-19 Clinics on their Attitudes towards Patient Safety - Gülhan Erkuş Küçükkelepçe; Yasemin Altınbaş; Türkan Karaca (Association of Nurse Managers, 2022)
Aim: This study aimed to investigate the effect of individual workload perceptions of nurses working in COVID-19 clinics on their attitudes towards patient safety. Method: The research was conducted in a descriptive and correlational type. The study sample consisted of 323 nurses working in COVID-19 clinics from different health institutions between February 15-April 15, 2021, in Turkey. 'The Individual Workload Perception Scale' and 'the 'Patient Safety Attitude Questionnaire' were used for the collection of the data analyzed with descriptive statistics, correlation analysis, and multiple linear regression analysis. Results: The nurses' mean Individual Workload Perception Scale score was 98.5+-18.7, and the Patient Safety Attitude Questionnaire score of nurses was 140.2+-27.5. There was a positive and statistically significant relationship between the nurses' Individual Workload Perception Scale and Patient Safety Attitude Questionnaire scores. A negative and statistically significant relationship was found between the Stress Recognition sub-dimension of the Patient Safety Attitude Questionnaire and the Workload and Intention to stay sub-dimensions of the Individual Workload Perception Scale. The effect of the nurses' individual workload perception on the attitude towards patient safety accounted for 53.2% of the total as a result of the regression analysis. Conclusion: The results obtained from the study show that nurses with positive individual workload perceptions also have positive attitudes towards patient safety. In line with the study results, nurse managers need to act as a bridge in meeting the training needs of the employees on issues requiring dynamic and continuous access to new information such as patient safety and for employees to access resources. Furthermore, it is recommended to conduct further studies using quantitative and qualitative research methods to gain a deeper understanding by revealing the stressors affecting nurses' workload perceptions in the work environment, their intention to stay, and performance.